Strategi Penanaman Karakter Tanggung Jawab melalui Pembelajaran PPKn sebagai Upaya Penguatan Nilai Kewarganegaraan Siswa Sekolah Menengah di Era Krisis Moral - Syakur Syakur; Asri Bariqoh; Mahin Ainun Naim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2025)
The decline in a sense of responsibility among teenagers has become an issue that has attracted attention and sparked controversy in the world of education, especially at the secondary school level. Pancasila and Civic Education (PPKn) is expected to be a strategic means of instilling values of responsibility and moral awareness in students. This study aims to explore strategies for instilling a sense of responsibility among students at Arrohmaniyah Tambelangan High School, Sampang. The research approach uses a qualitative method with a case study design. The research subjects are 30 purposively selected 11th grade students. Data were collected through interviews, observations, and documentation, then analyzed using thematic analysis techniques to identify internal and external factors that influence the formation of responsible character. The results showed that the instillation of responsible character was influenced by students' self-motivation, teachers' exemplary behavior, parental support, and a conducive school culture. Collaboration between schools and families proved to be a key factor in fostering consistent responsible behavior. These findings emphasize the importance of Civic Education as a solution to the crisis of students' moral responsibility (emergency) while also being in line with the trend of character education in the era of the Merdeka Curriculum.